Regularization and Fourier Series for Fredholm Integral Equations of the Second Kind with a Weakly Singular Kernel. (2nd January 2018) - Guebbai, Hamza
ABSTRACT: To compute an approximate solution, of a weakly singular integral equation, we first regularize the kernel, and then truncate the associated Fourier series. An application to an astrophysical transfer equation is presented.